Stack 'em high, pitch 'em low. - Ince, Darrel (Times Higher Education Supplement, 1999)
Discusses the negative effects of the increasing number of books dealing with computers and other related issues. Characteristics of books on computers; Trend of employers' preferring training qualifications to computing degrees; Books' emphasis on the importance of software issues; Development of programmers unable to program.